2023
DOI: 10.3390/mi14040799
|View full text |Cite
|
Sign up to set email alerts
|

A Long-Term Monitoring Method of Corrosion Damage of Prestressed Anchor Cable

Abstract: Based on high-stress characteristics of prestressed anchor cables, this paper develops an axial-distributed testing method to test corrosion damage of prestressed anchor cables. The positioning accuracy and corrosion range of an axial-distributed optical fiber sensor is studied, and its mathematical model between corrosion mass loss and axial fiber strain is established. The experimental results show that the fiber strain from an axial-distributed sensor enables one to reflect the corrosion rate along a prestr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Earth pressure box [102][103][104][105][106][107] Distributed optical fiber [108][109][110] Anchor point failure Distributed optical fiber [111][112][113][114][115] The failure distress of the anchorage point of a subgrade retaining structure refers to the phenomenon that the anchorage point in a subgrade retaining structure is damaged or failed. Anchorage points are usually used to fix subgrade retaining structures to resist the thrust and lateral force of soil.…”
Section: Structure Type Distress Sensor Referencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Earth pressure box [102][103][104][105][106][107] Distributed optical fiber [108][109][110] Anchor point failure Distributed optical fiber [111][112][113][114][115] The failure distress of the anchorage point of a subgrade retaining structure refers to the phenomenon that the anchorage point in a subgrade retaining structure is damaged or failed. Anchorage points are usually used to fix subgrade retaining structures to resist the thrust and lateral force of soil.…”
Section: Structure Type Distress Sensor Referencesmentioning
confidence: 99%
“…Il-Bumkon and Yong-seokkon et al [113,114] put forward a method to monitor the anchorage force by measuring the strain field on the bearing plate with distributed optical fiber sensors and, through experiments, showed that the anchorage force has a great correlation with the strain distribution on the bearing plate. Li Jianzhi et al [115] Figure 13. Site construction of the anti-slide pile (figures are reproduced from Wei et al [110]).…”
Section: Distributed Optical Fibermentioning
confidence: 99%
See 1 more Smart Citation